Evaluating the 'Gerbang Kembar' Program for Out-of-School Children: Lessons from Pasuruan Regency, Indonesia on Aligning SDG 4 and SDG 8 - Mokhammad Syamsudin; Warih Handayaningrum; Sri Setyowati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To evaluate the strategy implemented by the Pasuruan Regency Education and Culture Office in addressing school dropouts to support the improvement of the Human Development Index (HDI) through the Gerbang Kembar Program. Method: This study employed a qualitative evaluative approach using the Context, Input, Process, and Product (CIPP) evaluation model. Data were collected through in-depth interviews, observations, documentation, and literature reviews. Data trustworthiness was ensured through source triangulation, technique triangulation, and member checking. The data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing and verification. Results: The findings indicate that, in the context dimension, the Gerbang Kembar Program was designed in accordance with community needs through a by name by address data-based approach, although it continues to face social, economic, and cultural challenges. In terms of input, the program is supported by adequate human resources, funding, infrastructure, and regulatory frameworks; however, limitations remain in staff competencies, disparities in educational facilities, and funding for direct interventions. Novelty: The novelty of this research lies in the comprehensive application of the CIPP evaluation model to assess the Gerbang Kembar Program as an evidence-based strategy for addressing Out-of-School Children (OSC) through a by-name, by-address approach. The study integrates policy implementation, program management, and socio-environmental factors to evaluate how the program contributes to expanding equitable access to education (SDG 4) while strengthening the foundation for future employability and inclusive economic participation (SDG 8) in Pasuruan Regency, Indonesia.